x(x-6) + 3(x-6)
x^2-6x + 3x-18
x^2 - 3x - 18
2006-11-16 12:14:11
·
answer #1
·
answered by Anonymous
·
0⤊
1⤋
use th FOIL method
F = multiply " first terms by firdt terms " = X times X = x^2
O + Multiply outside terms by outside terms = X times _6 = -6x
I = multiply indide terms by inside terms + 3 times X = 3 x
L = multiply last terms by last termd = 3 times -6 = - 18
combine this into
x^2 + ( -6x) = ( 3x) = 1( - 18 )
combine like terms
x^2 - 3x_ 18
2006-11-16 12:30:36
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
(x + 3) (x - 6)
= x^2 -18 +3x -6x (multiply two algebraic expressions)
= x^2 -3x -18 (put variables together and contant terms
together)
2006-11-16 12:16:16
·
answer #3
·
answered by frank 7
·
0⤊
0⤋
If you mean what is this multiplied out than you would use FOIL to solve it.
(x+3)(x-6)
x^2-6x+3x-18
x^2-9x-18
2006-11-16 12:15:14
·
answer #4
·
answered by brads 2
·
0⤊
1⤋
use the FOIL method on this problem. First numbers, Outside numbers, Inside numbers, Last numbers. so your answer would be x^2-3x-18
2006-11-16 12:31:38
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
(x + 3)(x - 6) = 0
x^2 - 3x - 18 = 0
QED
2006-11-17 07:37:53
·
answer #6
·
answered by CSUFGrad2006 5
·
0⤊
0⤋
x^2 - 3x - 18
2006-11-16 12:18:42
·
answer #7
·
answered by emilyy :] 3
·
0⤊
0⤋
x^2 - 3x - 18
2006-11-16 12:16:14
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋
x^2 -3x-18 Use FOIL. (Multiply first terms of each) + (Multiply outer) + (Multiply inner) + (Multiply last terms)
2006-11-16 12:16:11
·
answer #9
·
answered by clouddragon10 1
·
0⤊
0⤋
x^2-6x+3x-18
your answer is x^2-3x-18
2006-11-16 12:14:10
·
answer #10
·
answered by LaMathrick B 2
·
0⤊
0⤋